A model for customer retention in electronic banking market - Ahmad Khosravi; Vahid Nasehifar; Tohfeh Ghobadi Lamuki; Alireza Islambolchi; Hossein Hajibabaei (Shahid Beheshti University of Medical Sciences, 2022)
Background: In a difficult competitive environment, timely and organized relationship with customers is the best way to increase customer satisfaction, increase sales and reduce costs. Methods: In a mixed method, interview was used in qualitative section and questionnaire was used in the quantitative section. The statistical population for the interview was 12 people and the statistical population of the quantitative section included 380 customers of Saderat Bank of Isfahan and Lorestan provinces that their total number was 37000. Measurement tools included a researcher-made questionnaire and an interview form. Data analysis was performed by regression test method in SPSS software. Results: The website, ease of use, information security, appropriate format, savings in time, and subjective norms were considered as effective variables of electronic banking services. The results indicated that each of the above components have a direct and significant relationship with customer retention. to save time, service offering systems should be used using the data of each customer and the information and the services provided without the need for the customer's presence in electronic services to improve performance of electronic banking as well as provide conditions for full competition in the market for banks to increase the performance of banks. Conclusion: Given the development pattern of customer retention in banking services, it is necessary to pay special attention to the importance of the effective factors listed by managers and employees.